OUTPUT GRAFIS UNTUK SISTEM PENDUKUNG KEPUTUSAN PADA PT. XYZ DALAM DESAIN APLIKASI REKAPITULASI PENJUALAN SALES - Susilowati, Meme (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2010)
In this study the author focuses on graphic design as a complement output tabular output for a recapitulation applications sales selling PT. XYZ. This is consistent with the goals of PT. XYZ is a manufacturing company that is developing, for that needed output as parameter manager within retrieve decisions development marketing area. Besides also there another destination namely simplify monitoring achievement mostly sales. Design of output in the application recapitulation sales salesman is based on direct observation and interviews with relevant parties. This research produces applications equipped facilities to record sales transactions its sales as primary data producer reports such graphics sale turnover nor tables sales salesman. Â Keywords: output, graphics, charts, sales, sales, decision